Stimulation of investment activities in the conditions of infrastructure restoration and country development - Zeltser, R.; Tytok, V. (Ways to Improve Construction Efficiency, 2022)
Today, Ukraine remains an investment-attractive country. The state has the potential to adequately respond to all these challenges, both new and inherited. Throughout the period of our struggle for independence, with the losses we suffered: human, industrial, loss of sales markets and traditional partners, the economy of Ukraine continues to work. Having lost some traditional advantages, we have gained new ones. The sphere of investments was and remains an object of joint interests of both the state and business. This is manifested in the search for sources and ways to increase the efficiency of investments, optimization of investment activities, analysis of investment success in various industries and in the economy as a whole. In this regard, the key importance in the development of the investment process belongs to the state. A necessary condition for the recovery of Ukraine’s economy is high investment activity. It is achieved by increasing the volume of realized investment resources and their most effective use in priority areas of the economy and social sphere. Investments form production potential on a new scientific and technical base and increase Ukraine’s competitive position on the world market. The problem of creating a favorable investment climate for attracting investments to the Ukrainian economy has become particularly acute in recent years. The relevant investment policy is supposed to play a decisive role in its solution. The government approved the draft law on simplifying the permitting procedures for acquiring the right to land and for starting construction during the implementation of projects aimed at restoring the economy. Also, Law of Ukraine No. 1116 dated February 17, 2022 "On State Support of Investment Projects with Significant Investments in Ukraine" (Law on Investment Nurses) entered into force, the purpose of which is to attract significant investments to the economy of Ukraine. In accordance with the Law and relevant amendments to the Tax and Customs Codes of Ukraine, a package of special investment incentives will be available for investment projects that meet certain requirements.